2005
DOI: 10.1002/cphc.200400273
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electronic Properties of Fullerenes C52q+: Is C522+ an Exception to the Pentagon Adjacency Penalty Rule?

Abstract: The structure, vibrational spectra and electronic properties of the neutral, singly and doubly charged C52 fullerenes were studied by means of the Hartree-Fock method and density functional theory. Different isomers were considered, in particular those with the lowest possible number (five or six) of adjacent pentagons, and an isomer with a four-atom ring. For neutral and singly charged species, the most stable isomer is that with the lowest number of adjacent pentagons, namely five. However, for C(52)2+, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…However, few theoretical studies have shown that nonclassical fullerenes, especially those containing 4-MRs, can compete with classical fullerenes in chemical stabilities. [14][15][16][17][18][19][20][21] We note that a nonclassical fullerene C 62 containing a 4-MR has been synthesized and detected experimentally. 21 There have been increasing research interests in small to medium-sized ͑n =20-36͒ carbon clusters since the discovery of the C 60 .…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, few theoretical studies have shown that nonclassical fullerenes, especially those containing 4-MRs, can compete with classical fullerenes in chemical stabilities. [14][15][16][17][18][19][20][21] We note that a nonclassical fullerene C 62 containing a 4-MR has been synthesized and detected experimentally. 21 There have been increasing research interests in small to medium-sized ͑n =20-36͒ carbon clusters since the discovery of the C 60 .…”
Section: Introductionmentioning
confidence: 86%
“…[7][8][9][10][11][12][13]17,[22][23][24][25][26][27][28][29][30][31] In our previous paper ͑Paper I 26 ͒, we studied relative stabilities of various isomers of carbon cluster C 20 using high-level ab initio methods. In that study, the bowl-shaped "fullerene fragment" corannulene was theoretically identified as the ground-state isomer of C 20 , which has a lower energy than the ͑only͒ classical fullerene isomer of C 20 . Indeed, the bowl-shaped isomer of C 20 has been experimentally detected in photoelectron spectroscopy ͑PES͒ experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the theoretical side, all mathematically possible classical isomers from C 20 to C 90 and beyond have been studied, and the consensus is that the stable classical isomers typically satisfy a more general rule, i.e., that pentagon adjacencies are minimized [3]. This has also been called the pentagon-adjacency-penalty rule (PAPR) [4,5]. The focus of studies of classical fullerenes is now moving on to applications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even for those non-IPR isomers, the ones with fewer pentagon-pentagon adjacencies are usually more stable than others, i.e. they obey pentagon adjacency penalty rule (PAPR) [8][9][10] . To our knowledge, the exceptions to IPR and PAPR are in the cases of C 72 [11] and C 50 [12] , respectively.…”
Section: Introductionmentioning
confidence: 99%